Analisa Pengecoran Logam dengan Pengujian Mekanik dan Metalografi - Handi Handi; Iwan Setiono; Waris Sudaryanto (Fakultas Teknik - Universitas Bung Karno, 2023)
The Ball Valve Axle is an axle that functions as a handle for the balls on HPD and HPS type hydrants produced by a metal foundry factory in Tegal, Central Java. This Ball Valve Axle is made from gray cast iron which consists of 2.746 percent carbon, 0.247 percent silicon, 0.708 percent manganese, 0.001 percent phosphorus, 0.058 percent sulfur, 0.007 percent chromium, 0.046 percent nickel, 0.172 percent molybdene, 0.000 percent vanadium, tungsten 0.007 percent, copper 0.122 percent, aluminum 0.003 percent, titan 0.003 percent, boron 0.00 percent, tin 0.026 percent, lead 0.000 percent and the element iron itself. In the casting process, porosity has occurred which causes the cast product to fail and cannot be used. To determine the condition of the failed object, tests are carried out, namely mechanical testing and metallographic testing. Mechanical tests carried out include material wear testing, material hardness with a hardening process through a heat treatment process at a temperature of 870 degrees Celsius which is then tempered at temperatures of 100 degrees Celsius, 200 degrees Celsius, 300 degrees Celsius and 400 degrees Celsius. Wear level The casting yield is 0.0001 mm2/kg and the hardness level is 166,360 kg/mm2. This cast iron experiences high hardness after being tempered at 100 degrees Celsius where the hardness becomes 418.347 kg/mm2 but experiences a decrease in hardness if we temper it to 400 degrees Celsius where the hardness becomes 270.813 kg/mm2.